Políticas de desarrollo humano en modelos de crecimiento económico dinámico, sostenible e inclusivo: Perú, 1990 –2020 - Varona Castillo, Luis (2024)
The research aims to determine the causality and cointegration relationship between economic growth and human development in Peru, from 1990 to 2020. The econometric methodology analyzes the short- and long-term impacts using an autoregressive distributed lag model (ARDL) and Error Correction Model (ECM). In conclusion, strong evidence has been found of a direct and statistically significant causality relationship at 1% with a positive coefficient (+1.23) between quality of life and economic growth, which shows a positive Granger causality and a direct cointegration relationship in the long term with the limits test (F- Bounds Test), both statistically significant at 1% respectively. Furthermore, investment and export growth explain economic growth with a direct and statistically significant causality at 1% (+0.18 and +0.22), respectively. The style of democracy explains economic growth with a negative and statistically significant causality at 1% (-0.09), which coincides with the “mining export boom” (2001-2013). Pro-human development policies are recommended, to boost economic growth. This involves expanding productive capacities, innovation, and public management, specifically quality in education and health. Create an appropriate environment to expand the quality of life that leads to better levels of productivity, strengthening social capital and expansion of freedoms with democracy as the best instrument.